DEVELOPMENTS IN COMPUTATIONAL FLUID DYNAMICS (CFD) RESEARCH FOR THERMAL COMFORT ANALYSIS IN BUILDINGS IN TROPICAL CLIMATES: A BIBLIOMETRIC STUDY OF 2016–2026 - Ef Syahrazzad Rafid; Susilo Kusdiwanggo (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
The application of Computational Fluid Dynamics (CFD) for evaluating thermal comfort in buildings located within tropical climates has become an important convergence between environmental engineering and sustainable architectural design. Existing studies, however, have not comprehensively mapped the intellectual development of this research domain, resulting in limited understanding regarding its thematic evolution, major contributors, and unresolved research gaps. This study presents a systematic bibliometric review of Scopus-indexed publications published between 2015 and 2026. Literature retrieval employed a search strategy combining keywords related to CFD or airflow simulation, thermal comfort or indoor air quality, and tropical or hot and humid climate contexts. Systematic screening based on relevance and language criteria reduced the initial corpus to a final dataset of 110 documents. Results indicate a consistent increase in scholarly output throughout the study period, with publication growth accelerating markedly after 2022. Malaysia and Indonesia emerged as the leading contributors to this body of knowledge. Thematic mapping further demonstrates that airflow simulation and indoor thermal performance represent well-established motor themes, whereas the application of CFD in vernacular and naturally ventilated tropical buildings remains an emerging research niche. Empirical validation was incorporated through field measurements and CFD simulations conducted in a naturally ventilated traditional market in Batu, East Java, Indonesia, serving as an illustrative case to address the identified research gaps. Findings confirm that building orientation alone does not ensure a uniform distribution of thermal comfort across multi-zone naturally ventilated public buildings, a building typology that continues to be underrepresented in the existing literature.